Municipal enterprises, institutions and organizations as subjects of administrative law - Yatsentiuk , Stanislav (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
This article delves into the examination of communal enterprises, institutions, and organizations from the perspective of their classification as subjects of administrative law. It is emphasized that communal enterprises, institutions, and organizations possess general characteristics inherent to all legal entities of public law, while also distinguishing themselves by their functional orientation and the entity responsible for their establishment (formation).Furthermore, it is concluded that they possess administrative legal personality, meaning they are bearers of subjective rights and obligations established by administrative legal norms, and are capable of realizing (fulfilling) such rights (obligations). It is underscored that the administrative legal personality of these subjects is a prerequisite for their administrative legal status, and its specificity lies in the fact that in administrative legal relations, they are represented and act through their head.It is noted that the head of a communal enterprise, institution, or organization directly manages such a legal entity, organizes its activities, ensures the fulfillment of tasks stipulated in the constituent document, bears responsibility for the non-fulfillment of these tasks, and also ensures the formation and heads its administration.A definitive characteristic of communal enterprises, institutions, and organizations as subjects of administrative law is proposed, according to which they are participants in administrative legal relations, founded (formed) by local self-government bodies on the basis of communal property, and possessing administrative legal personality. These subjects become participants in administrative legal relations in the performance of a specific duty or at their own discretion, and their activities or certain aspects of their functioning are subject to comprehensive administrative legal regulation.